2019
DOI: 10.1002/jper.19-0051
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal inflammation is related to increased serum calcitonin gene‐related peptide levels in patients with chronic migraine

Abstract: Background Recently, a relationship was found between periodontitis and chronic migraine. Calcitonin gene‐related peptide (CGRP) is a key element in migraine pathophysiology. However, no information exists of the potential association between periodontal inflammation and CGRP in chronic migraine. The aim of the study was, therefore, to investigate whether there is a link between periodontitis and peripheral levels of CGRP in a cohort of patients with chronic migraine. Methods We included 102 chronic migraineur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…For comparison group f, ictal vs interictal also refers to the active cluster bout vs remission. In addition to the references from Table 3 with clear blood specimen descriptions (n = 30), 15 references were included 21,26,27,37,39,43,48,125‐132 . Abbreviations: chronic cluster headache (CCH); chronic migraine (CM); control (CTRL); episodic cluster headache (ECH); female/female‐dominated (F/FD); migraine (M); both sexes (M/F); male/male‐dominated (M/MD); migraine with aura (MWA); migraine without aura (MWoA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison group f, ictal vs interictal also refers to the active cluster bout vs remission. In addition to the references from Table 3 with clear blood specimen descriptions (n = 30), 15 references were included 21,26,27,37,39,43,48,125‐132 . Abbreviations: chronic cluster headache (CCH); chronic migraine (CM); control (CTRL); episodic cluster headache (ECH); female/female‐dominated (F/FD); migraine (M); both sexes (M/F); male/male‐dominated (M/MD); migraine with aura (MWA); migraine without aura (MWoA).…”
Section: Resultsmentioning
confidence: 99%
“…(B) Meta‐analysis of CGRP in episodic and chronic migraine (cases) compared with CTRL. Imputation of missing standard deviation (SD) was done for Leira et al 132 A FD/MD case group means that ≥70.0% of the cases were females/males (case average), thereby sex refers to the sex distribution in the case group. When information was not available for the studies within the subgroup, information from the entire study was used to evaluate sex distribution and age.…”
Section: Resultsmentioning
confidence: 99%
“…A recent case-control study showed that subjects with periodontitis had two-fold increased risk for having chronic migraine 15 . On top of that, another clinical study demonstrated that periodontal inflammation was associated with increased circulating levels of CGRP in chronic migraineurs and authors hypothesized that upregulation of IL-6 could mediate this finding 3 . However, whether IL-6 induces CGRP overexpression or vice versa is still unknown as CGRP is capable of producing inflammatory cytokines from lymphocytes and macrophages after lipopolysaccharide infection 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Study design. This is a secondary analysis with a cross-sectional design from previous observational studies from our group, which looked at the clinical and molecular relationship between periodontitis and chronic migraine 3,15 .…”
Section: Methodsmentioning
confidence: 99%
“…These are mechanisms that are considered to be close to LA development. [14][15][16][17] We compared the results of sTWEAK with other potential biomarkers for predicting hemorrhagic transformation of ischemic stroke 8 ; those related to inflammation and oxidative stress processes namely leukocytes, fibrinogen, C-reactive protein, erythrocyte sedimentation rate, serum levels of interleukin 6 (IL-6), and tumor necrosis factor alpha (TNFa) 25,26 ; those correlating with BBB disruption such as microalbuminuria, matrix metalloproteinase-9 (MMP-9), serum levels of S100-b, neuron-specific enolase (NSE), and neuroserpin 27,28 ; those involved in vasoreactivity including cell fibronectin (c-Fn), endothelin-1 (ET-1), and platelet-derived growth factor-CC isoform (PDGF-CC) 29,30 ; and finally, those related to serum levels of glutamate were determined as an excitotoxicity marker. 31 Blood samples to measure biomarkers were obtained before administering the reperfusion treatment.…”
Section: Biomarkersmentioning
confidence: 99%